Green technology on the virgin coconut oil production using enzyme from pineapple waste - Harimurti, Sabtanti; Nadhifa, Naurah; Febrianti, Fera Rizki; Pramana, Facetha Intan; Wahita, Sevina Riska; Sukamdi, Dyani Primasari; Krisridwany, Annisa; Widada, Hari; Amid, Azura (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Virgin coconut oil (VCO) is widely used for the pharmaceutical and cosmetic industries. The high lauric acid content is very beneficial in the pharmaceutical field, such as for antiviral and antibiotic. Also, this VCO is very useful for cosmetic formulation. VCO production can be done by several methods, which are chemical, physical, and enzymatic methods. By the increase of VCO demand at the national and international levels, this study proceeded with the production of VCO using an enzymatic way that was efficiently conducted and environmentally friendly. The purpose of this research is to study the enzymatic process of VCO production by using pineapple waste, including pineapple crowns, pineapple fruit skins, pineapple leaves, and pineapple trunks. The pineapple waste used contains the enzyme bromelain to break down protein emulator in coconut milk cream. From the number of experiments with variations in substrate volume and temperature, the optimal VCO formation was obtained at 50oC with the ratio between the substrate and enzyme material was 9 to 1. The quality of VCO was evaluated as water content, free fatty acid concentration, and saponification numbers. Based on the evaluation results, the quality of VCO produced was similar to the standard of APCC, SNI, and Codex.